EVALUASI MANAJEMEN BERBASIS SEKOLAH (MBS)DI SMP NEGERI BOJA KABUPATEN KENDAL - Rita Widjajanti; Bambang Suteng Sulasmono (Universitas Kristen Satya Wacana, 2015)
The study aimed to evaluate 1) whether the PAKEM plan carried out as a fulfillment of the standardized goal-oriented learning plan. 2) The performance of PAKEM learning carried out looking into whether it is in accordance with the goal-oriented plans. 3)The outputs of PAKEM learning, measured by the achievement of the learning objectives. The research conducted here has applied an evaluative approach using both quantitative and qualitative methodology. This research was conducted in SMPN 2 Boja Kendal regency. The respondents assigned to the research were principal, 20 classroom teachers of IX grade and 30 students of class IX C. The data collection techniques used observation, documentation study and interview. The quantitative data analysis was conducted to gain the results of the data of observation and of studying the documents, whereas the qualitative data analysis was carried out to examine the results of the interviews. The research showed that (1) the PAKEM learning plan carried out had fulfilled the standardized goal-oriented learning plan. Nevertheless, the teachers’ competence in selecting and making use of teaching media needs improving. Teachers as individuals or with the support of school may do this either. (2) The performance of PAKEM learning carried out has been done well in accordance with the goal-oriented plan because all the teachers have achieved good grades of teaching performance. However, to enhance their teaching performance, it is necessary for the teachers to improve their competence in making use of the available learning and teaching sources, teaching media and in assessing the students learning. (3) The outputs of PAKEM learning have been able to measure the goal achievement of learning. This has been proven by the fact that a lot of students have passed most of the school subjects (8 subjects) achieving grades higher than the minimum grades required to pass them. Referring to the minimum grade required to pass the subjects, only a few students have not passed 4 of them. Nevertheless, school needs to gradually raise the minimum passing grade in order to be equal to the national one.